Liquid-liquid phase separation drives immune signaling transduction in cancer: a bibliometric and visualized study from 1992 to 2024 - Pei, Yanhong; Liang, Haijie; Guo, Yu; Wang, Boyang; Wu, Han; Jin, Zhijian; Lin, Shanyi; Zeng, Fanwei; Wu, Yifan; Shi, Qianyu; Xu, Jiuhui; Huang, Yi; et al. (Frontiers in Oncology, 2025)
BackgroundLiquid–liquid phase separation (LLPS) is a novel concept that could explain how living cells precisely modulate internal spatial and temporal functions. However, a comprehensive bibliometric analysis on LLPS and immune signaling processes in cancer is still scarce. This study aims to perform a bibliometric assessment of research to explore the landscape of LLPS research in immune signaling pathways for cancer.MethodsUtilizing the Web of Science Core Collection database and multiple analysis software, we performed quantitative and qualitative analyses of the study situation between LLPS and immune signaling in cancer from 1992 to 2024.ResultsThe corresponding authors were primarily from China and the USA. The most relevant references were the “International Journal of Molecular Sciences”, “Proteomics”. The annual number of publications exhibited a fast upward tendency from 2020 to 2024. The most frequent key terms included expression, separation, activation, immunotherapy, and mechanisms. Qualitative evaluation emphasized the TCR, BCR, cGAS-STING, RIG-1, NF-κB signaling pathways associated with LLPS processes.ConclusionThis research is the first to integratively map out the knowledge structure and forward direction in the area of immune transduction linked with LLPS over the past 30 years. In summary, although this research area is still in its infancy, illustrating the coordinated structures and communications between cancer and immune signaling with LLPS within a spatial framework will offer deeper insights into the molecular mechanisms of cancer development and further enhance the effectiveness of existing immunotherapies.